f ( x ) = ⎩ ⎪ ⎨ ⎪ ⎧ 0 + β : ⌊ x ⌋ ≡ 0 m o d 3 1 + β : ⌊ x ⌋ ≡ 1 m o d 3 2 + β : ⌊ x ⌋ ≡ 2 m o d 3
There is a unique value of β such that n = 1 ∑ ∞ 3 n f ( 3 n 2 0 1 7 ) = 0 . This value of β can be expressed as a − b c , where a , b , and c are positive integers and c is square-free. Find a + b + c .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Consider the ternary expansion of 2 0 1 7 .
2 0 1 7 = 4 4 + k = 1 ∑ ∞ 3 k a k
Where a k ∈ { 0 , 1 , 2 } . If follows that
⌊ 3 n 2 0 1 7 ⌋ = ⌊ 4 4 × 3 n + 3 n − 1 a 1 + 3 n − 2 a 2 + … + 3 a n − 1 + a n + 3 − 1 a n + 1 + … ⌋ = 4 4 × 3 n + 3 n − 1 a 1 + 3 n − 2 a 2 + … + a n
(Since ∑ i = n + 1 ∞ 3 i a i < 1 if a j < 2 for any j > n + 1 . This is the case since otherwise 3 n 2 0 1 7 is an integer, which is impossible)
Since all terms except a n are multiplied by a power of 3 , the value of f ( 3 n 2 0 1 7 ) is determined exclusively by the value of a n . It is easy to then see that f ( 3 n 2 0 1 7 ) = a n + β
We then get that our sum is
0 = n = 1 ∑ ∞ 3 n f ( 3 n 2 0 1 7 ) = n = 1 ∑ ∞ 3 n a n + β = 2 β + n = 1 ∑ ∞ 3 n a n
Our last infinite sum is easily evaluated by how we defined a n
0 = ( 2 0 1 7 − 4 4 ) + 2 β ⇒ β = 8 8 − 2 2 0 1 7
And so we get that a + b + c = 2 1 0 7
Problem Loading...
Note Loading...
Set Loading...
Define f 0 ( x ) = ⎩ ⎪ ⎨ ⎪ ⎧ 0 1 2 if ⌊ x ⌋ ≡ 0 mod 3 if ⌊ x ⌋ ≡ 1 mod 3 if ⌊ x ⌋ ≡ 2 mod 3 Then f ( x ) = α ( f 0 ( x ) + β ) , and the given sum is α ( n = 1 ∑ ∞ 3 n f 0 ( 3 n 2 0 1 7 ) + β n = 1 ∑ ∞ 3 n 1 ) . Since f 0 ( 3 − n N ) is precisely the n th digit in the ternary representation of N , the bracketed term on the left is equal to the fractional part of 2 0 1 7 , which is equal to 2 0 1 7 − 4 4 .
Next, note that ∑ n = 1 ∞ 1 / 3 n = 1 / 2 .
Combining these, the sum simplifies as α ( [ 2 0 1 7 − 4 4 ] + 2 1 β ) = 0 ; β = − 2 ( 2 0 1 7 − 4 4 ) = 8 8 − 2 2 0 1 7 , so we post a + b + c = 8 8 + 2 + 2 0 1 7 = 2 1 0 7 .